Tapered vs. Uniform Tube-Load Modeling of Blood Pressure Wave Propagation in Human Aorta - Mousavi, Azin; Tivay, Ali; Finegan, Barry; McMurtry, Michael Sean; Mukkamala, Ramakrishna; Hahn, Jin-Oh (Frontiers in Physiology, 2019)
In this paper, tapered versus uniform tube-load models are comparatively investigated as mathematical representation for blood pressure (BP) wave propagation in human aorta. The relationship between the aortic inlet and outlet BP waves was formulated based on the exponentially tapered and uniform tube-load models. Then, the validity of the two tube-load models was comparatively investigated by fitting them to the experimental aortic and femoral BP waveform signals collected from 13 coronary artery bypass graft surgery patients. The two tube-load models showed comparable goodness of fit: (i) the root-mean-squared error (RMSE) was 3.3+/-1.1 mmHg in the tapered tube-load model and 3.4+/-1.1 mmHg in the uniform tube-load model; and (ii) the correlation was r=0.98+/-0.02 in the tapered tube-load model and r=0.98+/-0.01 mmHg in the uniform tube-load model. They also exhibited frequency responses comparable to the non-parametric frequency response derived from the aortic and femoral BP waveforms in most patients. Hence, the uniform tube-load model was superior to its tapered counterpart in terms of the Akaike Information Criterion (AIC). In general, the tapered tube-load model yielded the degree of tapering smaller than what is physiologically relevant: the aortic inlet-outlet radius ratio was estimated as 1.5 on the average, which was smaller than the anatomically typical radius ratio of 3.5 between the ascending aorta and femoral artery. When the tapering ratio was restricted to the vicinity of the anatomically typical value, the exponentially tapered tube-load model tended to underperform the uniform tube-load model (RMSE: 3.9+/-1.1 mmHg; r=0.97+/-0.02). It was concluded that the uniform tube-load model may be more robust and thus preferred as the representation for BP wave propagation in human aorta; compared to the uniform tube-load model, the exponentially tapered tube-load model may not provide valid physiological insight on the aortic tapering, and its efficacy on the goodness of fit may be only marginal.